BASED ON TIKTOK: EXPLORING THE LINGUISTIC DIMENSIONS OF ENGLISH SLANG IN SOCIAL MEDIA - Aidil Syah Putra; Bahar, Aulia Aldilah; Unzila Alzura Fauzi (Media Inovasi Pendidikan dan Publikasi, 2024)
This study looks at the increasing slang use on TikTok and how it impacts language usage and communication styles. This study aims to provide light on the emergence of linguistic innovation in digital youth culture by examining the beginnings, propagation, and evolution of slang on TikTok. This study also investigates the sociolinguistic impact of TikTok slang on social interaction, identity formation, and cross-cultural communication. A qualitative descriptive method was used to find and analyze slang in videos and comments on TikTok. The result showed that slang on TikTok serves as social currency, a tool for creative expression, and driver for development of a new language in the modern digital communication word. This study found that TikTok slang plays an important role in shaping the social identity and interaction patterns of its users.